Simulating social work practice online with digital storytelling: challenges and opportunities. Issue 6 (18th August 2018) - Goldingay, Sophie; Epstein, Sarah; Taylor, Darci
ABSTRACT: To help prepare students for the challenges of modern social work practice, a regional Australian University's social work teaching team developed a client-centered web-based digital storytelling case study as a form of practice simulation (hereafter referred to as a digital case study) for use in a Master of Social Work qualifying program. A mixed methods evaluative study was completed. Descriptive statistics and a contextualist thematic analysis was undertaken on anonymous survey data collected from two cohorts ( n  = 29). Analysis demonstrated the learning benefits went beyond subjective confidence, toward mastering new skills consistent with course threshold concepts. Skill development in these areas meant students developed ways to self-manage and reflect on their emotional reactions to confronting and overwhelming situations without harming real clients. Nevertheless, during the digital case study trial, students found the discussion of controversial or sensitive issues in the online learning environment difficult. Other challenges identified included avoiding a sense of being overwhelmed by clients' multiple challenges, and not being able to interact with the simulated 'client' to ask further questions.